Assessment of morphological and biochemical characters of date palm culti vars (Indian Journal of Arid Horticulture, 2017)
Eight date palm cultivars i.e. Khadrawy, Shamran, Zahidi, Braim, Chipchap, Sabiah, Seddami and Medjoolcommonly grown in Bikaner were studied for their morphological and physiochemical characters at ICAR-CIAH, Bikaner,Rajasthan, India during the year 2015-16. The results revealed that differences in vegetative characters were statisticallysignificant except in the length of leaves. The fruit colour, size, weight, stone size and grooves in stone are useful charactersfor identification of date palm cultivars and the maximum plant height (5.34 m) and length of pinnae (44.79 cm) wasrecorded in cv. Seddarni whereas, minimum height (2.16 m) and length of pinnae (33.64 cm) in cv. Khadrawy. Breadth ofpinnae range from 1.96 cm in cv. Shamran to 2.85 cm in Medjool. Maximum leave length (3.25 m) was recorded in cv.Braim whereas, minimum in cv. Medjool (2.40 m). Among the varieties maximum fruit size i.e. length (4.41 cm), dia (2.92cm), fruit weight (21.49 g), stone weight (1.97 g) and pulp: stone ration (12.93) was produced by cv. Medjool and minimumfruit size i.e. fruit length (2.91 cm), diameter (1.93 cm), fruit weight (7.62 g) and stone weight (1.09 g) in cv. Sabiah . Thetotal soluble solid (36.55 % ), total sugars (36.35% ), reducing sugar (31.54%) was recorded maximum in Braim whereas,minimum total soluble solid (32.83 %) and reducing sugar (27.72%) in a Sabiah, total sugars (31.39%) in cv Shamran. Nonreducing sugars were maximum (5.50%) in a Seddami and minimum in cv. Shamran (2.70%). Maximum acidity content wasrecorded (0.31 %) in Sabiah and minimum (0.21 %) in Braim, maximum ascorbic acid was recorded in Medjool (7.83mg/lO0g pulp) and minimum in Shamran (4.65 mg/100 g).
Keywords: date palm; morphological and biochemical characters